A fair electronic payment system for digital content using elliptic curve cryptography. Issue 1 (March 2018) - Kang, Baoyuan; Shao, Dongyang; Wang, Jiaqiang
With rapid development of information and communication technologies purchasing digital content through the Internet has been greatly increased. Therefore, secure and fair electronic payment systems are important issue. To reduce system computational, communication and storage costs in many existing electronic schemes, Yang et al. recently proposed a novel electronic payment system based on authenticated encryption technology. But, Chaudhry et al. showed that Yang et al.'s electronic payment system is vulnerable to impersonation attack. Furthermore, Chaudhry et al. proposed improved electronic payment system. But, in this paper we point that Chaudhry et al.'s improved electronic payment system does not satisfy anonymity and fairness properties and the dispute resolution means in Chaudhry et al.'s electronic payment system are not effective. Furthermore, combining authenticated encryption and verifiably encrypted signatures technologies, we propose an improvement on Chaudhry et al.'s electronic payment system. Compared with Chaudhry et al.'s electronic payment system, the major changes of the proposed electronic payment system are in exchange phase. In this phase the private key and public key of the user are not needed, and the user generates verifiably encrypted signatures on his payment voucher. These changes guarantee the user anonymity, eliminate the advantages of the merchant, ensure the fairness of the payment system and the effectiveness of the dispute resolution phase. We also give the comparisons of proposed electronic payment system with some existing electronic payment systems.